Linguodidactics As a Methodological Basis For Teaching Foreign Languages (Eurasian Journal of Learning and Academic Teaching, 2024)
There is a separate field in linguistics called linguodidactics. Linguodidactics studies the processes of language learning and teaching, as well as develops methods and approaches that help to effectively master foreign languages. In this article, we will consider the main definitions, goals and objectives of linguodidactics, as well as the role of this science in the educational process. We will also discuss the methods and approaches used in linguodidactics and consider the trends of its development